Mystery of the hidden house - Blyton, Enid (London: Hodder Children's Books, 1943)
The Find-Outers are forbidden to solve any mysteries this summer, so instead they make one up for Mr Goon's nephew, Ern. But they don't expect their fake mystery to turn into a real one, or for Ern to disappear ...
Keywords: Children's stories; Fiction